Implementation of the Right to Disconnect and Workers’ Rights in Indonesia: Penerapan Right To Disconnect dan Hak-Hak Pekerja di Indonesia - Yustika Ardhany; Elfian Fauzy; Fatma Reza Zubarita (Universitas Islam Indonesia, 2023)
Undefined working hours and no boundaries between work-life balance are problems experienced by workers today. This research aims to first, examine the urgency of the possible implementation of the right to disconnect; secondly, provide a concept regarding the possibility of implementing the right to disconnect as an effort to fulfill and protect workers' rights in Indonesia. The research method used is the normative juridical method with statutory, comparative, and conceptual approaches. The results of this research are: first, the urgency that drives the implementation of the right to disconnect, namely; a) philosophically, the idea of the right to disconnect has been mandated by Pancasila and the 1945 Constitution of the Republic of Indonesia; b) sociologically, the phenomenon of work flexibility without limiting working hours causes health and psychological problems; c) juridically, provisions regarding working hours regulations for workers in the digital era have not been regulated comprehensively; secondly, the concept of the possibility of implementing the right to disconnect in Indonesia can be regulated through law. This research recommends adding a phrase containing the right to disconnect provision in the Labor Law.Keywords: Right to Disconnect, Fulfillment, Protection, Workers. AbstrakJam kerja yang tidak terbatas dan tidak adanya batasan antara kehidupan pribadi dan kehidupan pekerjaan menjadi permasalahan yang dialami oleh seorang pekerja saat ini. Penelitian ini bertujuan untuk pertama, mengkaji urgensi kemungkinan penerapan right to disconnect; kedua, memberikan konsep mengenai kemungkinan penerapan right to disconnect sebagai upaya pemenuhan dan perlindungan terhadap hak pekerja di Indonesia. Metode penelitian yang digunakan yaitu metode yuridis normatif dengan pendekatan perundang-undangan, perbandingan, dan konseptual. Hasil dari penelitian ini yaitu: pertama, urgensi yang mendorong penerapan right to disconnect yaitu; a) secara filosofis, gagasan right to disconnect telah diamanatkan oleh Pancasila dan UUD NRI 1945; b) secara sosiologis, fenomena fleksbilitas kerja tanpa membatasi jam kerja menyebabkan permasalahan kesehatan dan psikologis; c) secara yuridis, ketentuan mengenai peraturan jam kerja untuk para pekerja di era digital belum diatur secara komprehensif; kedua, konsep dari kemungkinan penerapan right to disconnect di Indonesia dapat diatur melalui UU. Penelitian ini merekomendasikan untuk menambahkan frasa yang memuat ketentuan right to disconnect di dalam UU Ketenagakerjaan.Kata Kunci: Right to Disconnect, Pemenuhan, Perlindungan, Pekerja.